Samotność pacjenta i lekarza wobec decyzji o leczeniu inwazyjnym w chirurgii - Rewakowicz, Maciej (Filozofia Chrześcijańska, 2015)
What we usually call loneliness is surely something experienced by: Palamedes and Ajax at Troy – the victims of Odysseus’s envy, Antygone – after meeting her sister Ismene, Prince Hamlet – after speeking to his mother. The author added to K. Jaspers b order situations his own loneliness research model: about invasive modality in surgery. It consists of two obligatory components parts: 1. Surgeon’s decision given to the patient in the form of proposal – suggestion. 2. Patient’s approval – consent. Without surgeon’s proposal – patient consent is meaningless. Without the patient’s approval, the operation cannot usually take place. Patient’s approval, or refuse, is this part of the surgical decision, were we can distinguish: 1. Man’s sovereignty in disposing of his health and life. 2. Existence of a distinct self – individuality of existence “I”. The research model reveals, perhaps even more clearly than the another ones, the ontic dimension of loneliness. Loneliness is the price of identity – oneselfness. In conclusions the author stressed: Necessity of discussing patient’s consent in conjunction with surgeon’s decision. Attempts to isolate the issue of patient’s approval lead to aporia, in particular cases to unhappiness. Whilst describing, by the surgeon, diagnosis and treatment plan, the patient does not gain any competence in the branch of surgery; he is preoccupied with examining the doctor. The most important thing is whether he can trust him. Even the best functioning institutions and community customs cannot remove loneliness completely, especially in border situation s. Therefore they may not be blamed for the fact that the loneliness exists. Time is a strong generator of tensions connected with loneliness. Agreeing with N. Hartmann, that the man exists in his achievements, the author adds: and in decisions made in solitude. There is also creativity here.